Bringing the Institutional Context Back In: A Cross-National Comparison of Alliance Partner Selection and Knowledge Acquisition - Vasudeva, Gurneeta; Spencer, Jennifer W.; Teegen, Hildy J. (Organization Science, 2013)
We suggest that firms' national institutional environments alter the logic of alliance partner selection and associated knowledge acquisition. We posit that cross-national variations in corporatist institutional structures (which reflect differences in underlying cooperative norms) influence the relative importance that firms place on a prospective partner's social value (evidenced from the partner's connectedness with members of its industry) and technological value (reflected in the technological complementarity and novelty of the partner's knowledge). We expect that as prospective partners' technological value increases, the probability of alliance formation increases the most for firms residing in less corporatist countries. Likewise, as prospective partners' social value increases, the probability of alliance formation increases the most for firms in more corporatist countries. We further argue that norms regarding knowledge acquisition within an alliance vary across countries, with deliberate learning approaches serving as the norm in less—not more—corporatist settings. We expect that such differences will lead to more immediate interpartner knowledge acquisition in less corporatist environments. Analysis of a longitudinal cross-national data set of alliances in the emergent fuel cell technology industry supports our arguments. Our findings highlight the significance of particular national institutions in specific organizational domains and the complementarity between institutional theory and other strategic resource-based perspectives in the context of interorganizational alliances.